A clinical profile of adverse drug reaction in HIV patients on highly active antiretroviral therapy - Nitish Ashok Gurav; K Ravi; B Sumana; Avinash Hannabe Rajanna; Rakesh Shetty Rajalbandi (Wolters Kluwer Medknow Publications, 2022)
Background: The expansion of antiretroviral therapy has increased the life expectancy of patients living with HIV (PLHIV). However, the Highly Active Antiretroviral Therapy (HAART) has a wide range of toxicity ranging from low grade intolerance to life threatening adverse drug reactions (ADR). Mild toxicity does not require any change in therapy. Moderate to severe toxicity may require substitution with an alternate class of drug while life threatening side effects need discontinuation of HAART till the condition of patient is stabilized and toxicity is resolved. Aim and Objective: To estimating the frequency of occurrence of ADRs in PLHIV on HAART. To estimate the clinical profile and severity of ADRs. Materials and Methods: The data of the patient who were registered at Centre of Excellence, Bowring and Lady Curzon Hospital, Bangalore Medical Collage & Research Institution, Bangalore, from May 2015 to April 2017, were retrospectively reviewed. Demographic data, routine blood investigations, ADRs and CD4 count at that time were noted. Results: In our study conducted from May 2015 to April 2017, 1834 PLHIV were included. Out of these patients, 1554 PLHIV were on HAART. 601 patients showed ADRs secondary to HAART. The age distribution was between 18 to 75 years and the mean age was 43.19+9.18. M: F:: 62:38. 409 patients had hypertriglyceridemia, 472 patients had hypercholesterolemia, 84 had hyperbilirubinemia, 48 developed anemia, 17 patients developed hepatotoxicity, 25 developed drug induced skin rash. Significant association was found between the above reactions and the causative drug. Other reactions like hyperglycemia, night mares, Steven Johnson syndrome (SJS) observed in the study did not show statistical significance. Conclusion: The commonly observed adverse drug reactions of HAART were hypertriglyceridemia, hypercholesterolemia, hyperbilirubinemia, anemia, hepatotoxicity and skin rashes. However hyperglycemia, SJS, night mares were rarely seen.